PERAN PENTING GURU DAN SEKOLAH DALAM PERKEMBANGAN BAHASA ANAK USIA DINI - Sisiliya Mareta; Novita Loka (I'tibar: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Language development is an important aspect for children's lives, especially in the era of global communication which uses language as a communication medium. This research aims to examine the role of teachers and schools in supporting children's language development. This research uses a qualitative method with a descriptive approach. Data collection was carried out through observation and analysis of the learning process at the IT Menarah Fitrah Indralaya Kindergarten in April-May 2024. The results of the research show that teachers and schools have a very important role in children's language development through various ways, such as being a model for good language use, provide language stimulation, create a language-rich environment, and provide direct instruction in language skills. Schools also provide a structured curriculum, trained teachers, access to resources, multilingual programs, and extracurricular activities that support children's language development. This research emphasizes the important role of teachers and schools in creating a conducive environment for children's language development from an early age